2014
DOI: 10.1371/journal.pone.0114011
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prediction on the Perception for Own-Race and Other-Race Faces

Abstract: Human beings do not passively perceive important social features about others such as race and age in social interactions. Instead, it is proposed that humans might continuously generate predictions about these social features based on prior similar experiences. Pre-awareness of racial information conveyed by others' faces enables individuals to act in “culturally appropriate” ways, which is useful for interpersonal relations in different ethnicity groups. However, little is known about the effects of predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 45 publications
(54 reference statements)
6
41
1
Order By: Relevance
“…Similar to previous studies (e.g., Ran et al, 2014b), the effect of prediction on the N170 was obtained by subtracting the N170 peak amplitudes in the predictable condition to those in the unpredictable condition for happy and angry faces of each participant.…”
Section: Methodsmentioning
confidence: 97%
“…Similar to previous studies (e.g., Ran et al, 2014b), the effect of prediction on the N170 was obtained by subtracting the N170 peak amplitudes in the predictable condition to those in the unpredictable condition for happy and angry faces of each participant.…”
Section: Methodsmentioning
confidence: 97%
“…Based on previous studies (Luo et al, 2013; Ran et al, 2014), the P1 component was analyzed via the following four electrode sites: O1/O2 and PO3/PO4. The amplitude of the positive peak of the EEG signal was quantified 50–110 ms after stimulus presentation.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental procedure was organized by E-PRIME 2.0. The current experiment employed the S1-S2 paradigm, which was used by previous researchers to explore the recognition of emotional faces ( Ran et al, 2014a , c ). On each trial of the experiment ( Figure 2 ), a fixation cross was shown for 100 ms. After the cross disappeared, the first facial emotional change video (S1) was presented for 600 ms. Next, a stimulus of house picture (a mask stimulus) was depicted for 100 ms.…”
Section: Methodsmentioning
confidence: 99%
“…To test these hypotheses, we adopted a S1-S2 paradigm, which was used by previous researchers to explore the recognition of emotional faces ( Ran et al, 2014a , c ; Li et al, 2017 ). Participants with HSA and LSA were instructed to perform a task of facial identity recognition, and their brain responses were recorded using high temporal resolution ERP techniques.…”
Section: Introductionmentioning
confidence: 99%